Formulation, Statistical Optimization And In Vitro Ex Vivo Characterization Of Enteric Coated Nanocarriers For Enhanced Oral Bioavailability Of A Bio-Pharmaceutically Challenged Drug - Panda, Subhranshu; Tikait, Shubham; Deshmukh, Swati (Journal of Neonatal Surgery, 2025)
Rifaximin, a Biopharmaceutics Classification System (BCS) Class II drug, exhibits poor aqueous solubility and limited systemic bioavailability following oral administration. The present study aimed to develop and optimize rifaximin-loaded enteric-coated solid lipid nanoparticles (RFN-EC-SLN) to enhance its oral absorption and therapeutic performance. A Quality by Design (QbD)-based Box–Behnken Design (BBD) approach was employed to optimize formulation variables, including lipid, surfactant, and polymer concentrations, with particle size, entrapment efficiency, and drug release as critical quality attributes. The optimized formulation (F6) demonstrated a mean particle size of 154 ± 2.6 nm, PDI of 0.21 ± 0.03, zeta potential of +17.5 ± 0.04 mV, and high entrapment efficiency (82.0 ± 1.6%). In vitro release studies revealed minimal drug release under gastric conditions (pH 1.2) and sustained release up to 86.0 ± 2.4% at intestinal pH (6.8), following zero-order kinetics (R² = 0.989). Stability studies conducted under accelerated conditions confirmed the physicochemical stability of the formulation. Acute toxicity evaluation in Wistar rats showed no mortality, behavioral abnormalities, or significant hematological and biochemical alterations, confirming systemic safety. Pharmacokinetic studies demonstrated significantly enhanced absorption of the SLN formulation, with increased Cmax, nearly two-fold higher AUC, prolonged half-life, and relative bioavailability of 159.3% compared to conventional rifaximin suspension. Overall, the developed enteric-coated SLN system effectively improved the solubility, intestinal protection, and oral bioavailability of rifaximin, highlighting its potential as a promising delivery platform for biopharmaceutically challenged drugs..